Toxicities Associated With Dose-Adjusted Epoch-R Compared With R-Chop as Frontline Therapy for Diffuse Large B-Cell Lymphoma: A Study Conducted in a Tertiary Level Hospital of Bangladesh - Rahman, Tanbin; Akter, Mafruha; Ara, Tasneem; Biswas, Akhil Ranjan; Kabir, Alamgir; Khan, Mohiuddin Ahmed (Bangladesh Journal of Medicine, 2022)
Background: Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma (NHL). This is a heterogeneous group of hematological malignancy of large B lymphocytes with a diffuse growth pattern. Managing DLBCL is challenging because of the biological and clinical heterogeneity of the disease and toxicities during treatment. Methods: This quasi experimental study was conducted at DMCH Hematology department from January 2018 to June 2019 including nineteen, newly diagnosed diffuse large B cell lymphoma with stage I to IV A/B cases. Protocol was approved by ethical review committee (ERC) of Dhaka Medical College Hospital(DMCH). Patients fulfilling the inclusion criteria were enrolled using convenient purposive sampling and then allotted any one of the two regimen groups. Results: Total nineteen (19) DLBCL cases were enrolled for this study and divided into two groups as arm A treated with RCHOP(10 cases) and arm B treated with RDA- EPOCH (9 cases) . Mean age of all patients was 41 years (range 16 to 60 Y). Among them majority (13/69%) of the patients were below 50 years of age and M: F ratio was 2:1.102 cycles of chemotherapy were administered among 20 patients. In R-CHOP group of patients, Grade 1-2 Anemia was found in 14 cycles (28.0%). In R-DA-EPOCH group Grade 1-2 Anemia was found in 14 cycles (31.1%). Grade 3-4 thrombocytopenia was found in 6 cycles (12%) in R-CHOP group. On the other hand, Grade 3-4 thrombocytopenia was found in 4(8.89%) patients in R-DA-EPOCH group. There were 4 episodes of neutropenic fever (8% of cycles) in R-CHOP group and 3 episodes (6.7% of cycles) in R-DA-EPOCH group. 8 out of 10 patients suffered from grade 1-2 anemia in R-CHOP group and 8 out of 9 patients suffered from grade 1-2 anemia. 2 out of 9 patients suffered from grade 3-4 thrombocytopenia in RDA- EPOCH group. Grade 3-4 hemorrhage occurred in 1(10%) patient in R-CHOP group and 2 (22.2%) patients in R-DA-EPOCH group. Mucocitis (grade 1-2) was found in 5 patients (50%) in R-CHOP group and 8 cycles (88.8%) in R-DA-EPOCH group which was not statistically significant. Diarrhea (grade 1- 2) was found in 2 patients (20%) in R-CHOP group and 5 patients (55.5%) in R-DA-EPOCH group. Neuropathy was found in 3 patients (30%) in R-CHOP group and 1 patient (11.1%) in R-DA-EPOCH group. Febrile neutropenia was found in 4 patients (40%) in R-CHOP group and 3 patients (33.3%) in R-DA-EPOCH group. Conclusion: From the result of this study it can be concluded that, Overall incidence of grade 3-4 anemia, thrombocytopenia and diarrhea was more in R-DA- EPOCH group and neuropathy was more common in R-CHOP group. Bangladesh J Medicine 2022; 33: 161-167